On the Curiosity of Philocrates (Ep. Arist. 1) - Druzhinina, Ekaterina (Hyperboreus, 2019)
The paper deals with a diﬃcult phrase from the beginning of the prologue of the Letter of Aristeas (Ep. Arist. 1), containing the information about Aristeas’ addressee Philocrates: διὰ τὸ σὲ περὶ πολλοῦ πεποιῆσθαι παρ’ ἕκαστα †ὑπομιμνήσκων† συνακοῦσαι. The manuscript reading ὑπομιμνήσκων is impossible and deﬁnitely corrupt. The emendations of Mendelssohn (ὑπομιμνήσκοντα) and Diels (ὑπομιμνήσκειν) imply that Philocrates constantly reminded Aristeas he would be glad to hear the story. Many modern scholars (Wright, Raurell, White) follow this interpretation. According to Zuntz, who corrected ὑπομιμνήσκων into ὑπομιμνήσκοντος, the phrase indicates that Philocrates was ready to listen to Aristeas, when he recalled what he had seen himself. We suggest that original reading was ὑπομιμνησκόντων and by underlining the curiosity and piety of Philocrates, the author wants to imply that his addressee is glad to listen when somebody reminds him what he already knows.